Promotion of sunflower growth under saline water irrigation by the inoculation of beneficial microorganisms - Pereira, Sofia I. A. (2017)
Soil salinization and fresh water scarcity are amongst the main environmental/agricultural problems, with serious consequences to plant productivity. Amelioration with microorganisms can enhance plant performance under salt conditions. The aim of this work was to evaluate the role of beneficial rhizospheric microorganisms on the growth of sunflower plants irrigated with salinized water with particular attention to nutrient balance and biochemical responses. Sunflower seedlings were inoculated with the arbuscular mycorrhizal fungi Rhizophagus irregularis, the rhizobacteria Chryseobacterium humi ECP37T, or the bacterial endophyte Ochrobacterium haematophilum ZR3-5, and with a mixed inocula of those microorganisms. Plant growth, nutrient accumulation and lipid peroxidation in plant tissues, and the activity of soil enzymes, were evaluated. Irrigating sunflower plants with saline water resulted in decreases in growth and negative effects in salt stress markers, however the application of bioinoculants enhanced biomass production and accumulation of K+, Mg2+, Ca2+, N and P, reduced Na+ levels in tissues and increased plant antioxidative response. This study contributes to devise inoculation strategies for sunflower cultivation in areas prone to salinization.